أثر القيادة التحويلية في جودة العمل الاداري : دراسة استطلاعية في الشركات العامة لصناعة الادوية و المستلزمات الطبية مصنع ادوية نينوى - د. محمد عبدالوهاب العزاوي; د. أحمد سليمان محمد الجرجري (PROSPECTIVE RESEARCHES, 2023)
Quality is one of the compititive advantages which organizations aim at achieving it. Quality covers most fields and aspects of the organization. Managerial work quality represents one of them in order to achieve this quality ,So it needs availability of many requirements and constituents which leadership style adopted by organization leaders which represents one of them, So this research tries to determine the effect of transference leadership in achieving managerial work quality by measuring the impact & correlation relationships between them according to analysing collected data by quationiar deleverd to a sample which includes (42) depts and unit heads in the general company for drugs industry & medical appliances /Ninavha medical factory. The research has come up with some conclusions; contribution of transferential leadership dimensions in manigerial work quality and exsisting secnificant impacts & correlations relationships of these dimintions in managerial work quality represent the most important one, among them. The research ends with to some suggestions which we see their importance to crease managerial work quality level via transferential leadership dimensions through affecting the communication, direction and the workers behavior inside the company to achieve the aims of each costumers, staffs, and company’s management as the same .